2011
DOI: 10.3727/096368910x550206
|View full text |Cite
|
Sign up to set email alerts
|

Collagen IV Significantly Enhances Migration and Transplantation of Embryonic Stem Cells: Involvement of α2β1 Integrin-Mediated Actin Remodeling

Abstract: Embryonic stem (ES) cell transplantation represents a potential means for the treatment of degenerative diseases and injuries. As appropriate distribution of transplanted ES cells in the host tissue is critical for successful transplantation, the exploration of efficient strategies to enhance ES cell migration is warranted. In this study we investigated ES cell migration under the influence of various extracellular matrix (ECM) proteins, which have been shown to stimulate cell migration in various cell models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Other studies have demonstrated an increased expression of AQP3 in skin carcinoma, increased AQP4 expression in glioblastoma and increased AQP5 expression in pancreatic and colon cancer (21)(22)(23)(24). Cell migration is affected by numerous factors; it is time-dependent (25), significantly enhanced by collagen IV in embryonic stem cells (26), and it has been observed that even a lesion can induce an increase in the migration of human neural progenitor cells (27). The findings from this study demonstrate that AQP5 knockdown reduced the migration of EC cells, suggesting that AQP5 is involved in the development of EC.…”
Section: Discussionsupporting
confidence: 57%
“…Other studies have demonstrated an increased expression of AQP3 in skin carcinoma, increased AQP4 expression in glioblastoma and increased AQP5 expression in pancreatic and colon cancer (21)(22)(23)(24). Cell migration is affected by numerous factors; it is time-dependent (25), significantly enhanced by collagen IV in embryonic stem cells (26), and it has been observed that even a lesion can induce an increase in the migration of human neural progenitor cells (27). The findings from this study demonstrate that AQP5 knockdown reduced the migration of EC cells, suggesting that AQP5 is involved in the development of EC.…”
Section: Discussionsupporting
confidence: 57%
“…Potential roles for ECMs in the stem cell niche and tumor microenvironment have been reported [12]. For example, COL4 significantly enhances the migration and differentiation of embryonic stem cells (ESCs) [13]. LAM is the most effective ECM for the maintenance of NSCs and GICs via its interaction with integrin α 6 [2], [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our integrated proteomics showed that the protein expression of any integrin β subunits was not significant in differentiated GICs, suggesting that the heterodimers with multiple integrin β subunits may support GIC differentiation via the RGD-binding motif. Integrin α 2 is expressed in ESCs and NSCs [22], and it stimulates cell adhesion/migration [13]. Integrin α 5 is also expressed on NSCs [22] and human gliomas [23].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, metastatic spreading of RAD001-resistant prostate cancer is accelerated by two strategies: (1) by upregulating the α 2 expression level (quantitative regulation) and (2) by strengthening the relevance of α 2 in controlling invasion (qualitative regulation). In fact, cell migration has been demonstrated to depend on the number of α 2 integrin receptors expressed on the cell surface (Li et al , 2011), as well as on qualitative parameters, such as activation of intracellular signalling cascades and/or receptor cross-talk (Ning et al , 2005; Sawhney et al , 2006). We assume that the conversion of prostate cancer cells from a drug-sensitive to a drug-insensitive state is accompanied by an elevated α 2 level, α 2–cytoskeleton interaction and cytoskeleton-related signalling, finally enforcing actin turnover and remodelling.…”
Section: Discussionmentioning
confidence: 99%